Analisis Yuridis Peran Otoritas Jasa Keuangan dalam Pengawasan Pasar Keuangan di Indonesia: Peluang dan Tantangan - Khotimah, Hilda Husnul; Iskandar, Eka Ardianto; Antoni , Herli (Prodi Tata Negara (Siyasah) IAIN Langsa, 2024)
The Financial Services Authority (OJK) and the Indonesian government are essential in regulating and monitoring financial markets, encompassing stock exchanges, currency trading, and capital markets, to uphold market integrity and safeguard investors against fraudulent operations. This legal research examines the regulatory architecture of financial markets, the procedures for oversight and enforcement, and inter-agency collaboration in the prevention of financial crimes. In the age of digital transformation, financial markets are progressively shaped by technological innovations and global financial trends. This research investigates the degree to which current regulations can accommodate these developments. Additionally, the efficacy of regulatory rules and their conformity with worldwide best practices are examined. This study examines the obstacles encountered by OJK and other financial regulators in maintaining market transparency, combating money laundering, and mitigating risks linked to digital financial services. The results demonstrate that regulatory harmonization, legal certainty, and improved cross-institutional coordination are essential components for fortifying financial governance in Indonesia. By cultivating an efficient and transparent financial ecosystem, regulatory authorities can maintain investor trust and guarantee financial market stability. This study suggests that ongoing regulatory enhancements, technological integration in oversight, and strong enforcement mechanisms are vital for mitigating rising risks in Indonesia's financial sector.